Is the Antiproteinuric Effect of Cyclosporine A Independent of Its Immunosuppressive Function in T Cells?. (13th June 2012) - Zhang, Bin; Shi, Wei
Abstract : The antiproteinuric effect of cyclosporine A(CsA) has been believed to result from its immunosuppressive effect on the transcription factor NFAT in T cells. However, current evidences supporting this hypothesis are missing. A recent study showed that CsA has a direct antiproteinuric effect on podocytes, suggesting a novel non-immunosuppressive mechanism for CsA's antiproteinuric effect. Conditional NFATc1 activation in podoyctes per se is sufficient to induce proteinuria in mice, indicating that NFAT activation in podocytes is a critical pathogenic molecular event leading to podocyte injury and proteinuria. Meanwhile, evidence showed that TRPC6-mediated Ca 2+ influx stimulates NFAT-dependent TRPC6 expression. Altogether, these advances in podocyte research indicate that calcineurin-NFAT signal or calcineurin-synaptopodin axis has a direct proteinuric effect on podocytes which raises the possibility of developing specific antiproteinuric drugs that lack the unwanted effects of calcineurin or NFAT inhibition.